Fingerprint of semi-crystalline structure memory in the thermal and ionic conduction properties of amorphous ureasil-polyether hybrid solid electrolytes - Palácio, Gustavo [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Royal Society of Chemistry (RSC), 2022)
Correlations among the structure, thermal properties, and ionic conductivity of solid polymer electrolytes (SPEs) were studied using a ureasil-polyethylene oxide (U-PEO) organic-inorganic hybrid prepared according to a simple sol-gel route, employing a low molecular weight PEO macromer (Mw = 1900 g mol−1). The behavior of an amorphous sample loaded with lithium triflate (LiTFSI) at an optimum ratio between ether oxygen and lithium (EO/Li+ = 15) was compared with that of a semicrystalline sample prepared without salt loading. The temperature range investigated by differential scanning calorimetry (DSC), Raman spectroscopy, small angle X-ray scattering (SAXS), and complex impedance spectroscopy covered both the glass transition and the melting temperature of the U-PEO. The gauche to trans conformational transformation of the (O-C-C-O)Li+ sequence showed similarity between the temperature evolution of the semi-crystalline U-PEO and amorphous U-PEO:Li+ samples, providing an indication of the local structural memory of crystalline state in the amorphous SPE. The linear thermal expansion of the average correlation distance between the siloxane crosslink nodes and the long-distance period of the lamellar semi-crystalline edifice were determined by SAXS. Comparison of the expansion curves suggested that although the siloxane nodes were excluded from the PEO crystalline edifice, the sharp expansion of the amorphous region between the lamellae during melting permitted modulation of the free volume of the hybrid network. In addition, the temperature-induced Li+-EO decomplexation observed by Raman spectroscopy explained the change of the average activation energy of the conduction process revealed by the different Arrhenius regimes. These results evidence the key role of the ionic conductivity decoupling from the segmental motion of chain pair channels on the improvement of ion mobility through the free volume between chains. This concept may inspire materials chemistry researchers to design optimized structures of polymer electrolytes with minimized structural memory of crystaline building blocks and improved ionic conductivity.